Prevalence of Aflatoxins in Camel Milk from the Arabian Peninsula and North Africa: A Reduction Approach Using Probiotic Strains - Tawfiq Alsulami; Mohamed G. Shehata; Hatem S. Ali; Abdulhakeem A. Alzahrani; Mohamed A. Fadol; Ahmed Noah Badr (Foods, 2023)
Camel milk is known as a source of nutritional and health supplements. It is known to be rich in peptides and functional proteins. One main issue facing it is related to its contamination, mainly with aflatoxins. The present study aimed to evaluate camel milk samples from different regions while trying to reduce its toxicity using safe approaches based on probiotic bacteria. Collected samples of camel milk were sourced from two main regions: the Arabic peninsula and North Africa. Samples were tested for their contents of aflatoxins (B1 and M1) using two techniques to ensure desired contamination levels. Additionally, feed materials used in camel foods were evaluated. Applied techniques were also tested for their validation. The antioxidant activity of camel milk samples was determined through total phenolic content and antioxidant activity assays. Two strains of probiotic bacteria (Lactobacillus acidophilus NRC06 and Lactobacillus plantarum NRC21) were investigated for their activity against toxigenic fungi. The result revealed high contamination of aflatoxin M1 for all samples investigated. Furthermore, cross-contamination with aflatoxin B1 was recorded. Investigated bacteria were recorded according to their significant inhibition zones against fungal growth (11 to 40 mm). The antagonistic impacts were between 40% and 70% against toxigenic fungi. Anti-aflatoxigenic properties of bacterial strains in liquid media were recorded according to mycelia inhibition levels between 41 to 52.83% against Aspergillus parasiticus ITEM11 with an ability to reduce aflatoxin production between 84.39% ± 2.59 and 90.4% ± 1.32 from media. Bacteria removed aflatoxins from the spiked camel milk in cases involving individual toxin contamination.